Extremely preterm infant weighing 350 g: too small to survive? - Ieva Šliaužienė; Vaida Aleksejūnė; Viktorija Ambroževičiūtė; Ilona Aldakauskienė; Rūta Jolanta Nadišauskienė; Rasa Tamelienė (Hygeia Press di Corridori Marinella, 2021)
Every year around 15 million premature neonates are born in the world, and this number is continuously increasing. The incidence of premature birth varies between 5% and 18% throughout the world. Despite advancements in medicine and technology and increased evidence-based diagnostic and treatment recommendations, prematurity is the most common cause of death among children under 5 years of age. The sequelae in the survivors of extreme prematurity are mental disability, cognitive impairment, cerebral palsy, blindness, deafness and chronic illness. Considering ethical and economic implications, neonatal survival and morbidity prognosis, resuscitation of neonates of borderline gestation differs in various countries and many international organisations do not recommend active resuscitation and treatment of newborns of up to 25 weeks of gestation. We present a case study of one of the smallest newborns in the world and the smallest newborn known to survive in Lithuania.